L’ Établissement hellénistique d’Ikaros-Faïlaka au Koweït - Mathilde Gelin (Arabian Humanities)
The French-Kuwaiti mission team studying the Hellenistic period at Failaka, conducted a first phase of work on the fortress from 2011 to 2018, with the objectives of completing the study of the fortifications, beginning that of the internal circulation, to clarify the chronology of the site, and to preserve the remains uncovered during its work and that of its predecessors. We present here some of the results obtained, which are still being exploited and should soon be published.